2019
DOI: 10.1177/2158244019833594
|View full text |Cite
|
Sign up to set email alerts
|

What Determines University Students’ Online Consumer Credit? Evidence From China

Abstract: In recent years, online consumer credit in China has boomed. Many Chinese undergraduates are interested in utilizing online consumer credit to meet their increasing consumption needs. However, the explosion in online loans to students has created many problems. Based on a survey of 286 undergraduate students from four universities in Beijing, the capital of China, this study provides an empirical analysis of the economic and social determinants of undergraduates' consumer credit. The estimation results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
4
14
2
Order By: Relevance
“…In that case, they are less willing to apply for campus loans and have lower loan amounts. This is the opposite of the findings in Hao et al (2019).…”
Section: Risk Perceptioncontrasting
confidence: 91%
See 1 more Smart Citation
“…In that case, they are less willing to apply for campus loans and have lower loan amounts. This is the opposite of the findings in Hao et al (2019).…”
Section: Risk Perceptioncontrasting
confidence: 91%
“…Based on a survey of college students in Henan Province, Yang & Wang (2019) found that campus loan behavior was influenced, in decreasing order from strong to weak, by personal behavior, lifestyle, and consumption desire. Meanwhile, based on a survey of 286 college students from four universities in Beijing, Hao et al (2019) found that campus loan demand was positively related to years of schooling, monthly living expenses, financial support from the university, and consumption preferences. However, parents' level of education, college major, and advertisements were found to have negative effects on campus loans.…”
Section: Literature Reviewmentioning
confidence: 99%
“…level, employment, household assets, household income, and family geographic location all had a significant impact on household debt. Based on a survey of 286 undergraduate students from four universities in Beijing, Hao et al (2019) conducted an empirical analysis of the economic and social determinants of undergraduates' consumer credit. However, that research was also not validated by the traditional peer-review process.…”
Section: September 2018mentioning
confidence: 99%
“…Surprisingly individuals with higher self-assessed numeracy levels are more likely to borrow, and business students (who also have higher levels of financial literacy) seem to borrow at a lower rate. Hao et al, (2019) similarly examine online consumer credit amongst students in Beijing.…”
Section: A Descriptive Statistics and Cross-sectional Determinates Omentioning
confidence: 99%
“…2 These young adults are technology-savvy and well accustomed to online purchasing. They represent a large market for retailers, and have been shown to be vulnerable to peer-pressure and conspicuous consumption decisions (O'Cass and McEwen, 2004;Podoshen, Li, and Zhang, 2011;Hao et al, 2019). Adverse decisions which can impact credit scores and indebtedness can manifest well into adulthood and have far reaching consequences.…”
Section: Introductionmentioning
confidence: 99%